Contrasting phenology of Eucalyptus grandis fine roots in upper and very deep soil layers in Brazil - Lambais, George Rodrigues; Jourdan, Christophe; de Cássia Piccolo, Marisa; Germon, Amandine [UNESP]; Pinheiro, Rafael Costa [UNESP]; Nouvellon, Yann; Stape, José Luiz; Campoe, Otávio Camargo; Robin, Agnès; Bouillet, Jean-Pierre; le Maire, Guerric; Laclau, Jean-Paul [UNESP] (Springer Nature, 2017)
Background and aims: While the role of deep roots in major ecosystem services has been shown for tropical forests, there have been few direct measurements of fine root dynamics at depths of more than 2 m. The factors influencing root phenology remain poorly understood, creating a gap in the knowledge required for predicting the effects of climate change. We set out to gain an insight into the fine root phenology of fast-growing trees in deep tropical soils. Methods: Fine root growth and mortality of Eucalyptus grandis trees were observed fortnightly using minirhizotrons down to a soil depth of 6 m, from 2 to 4 years after planting. Results: In the topsoil, the highest live root length production was during the rainy summer (20 cm m−2 d−1) whereas, below 2 m deep, it was at the end of the dry winter (51 cm m−2 d−1). The maximum root elongation rates increased with soil depth to 3.6 cm d−1 in the 5–6 m soil layer. Conclusions: Our study shows that the effect of the soil depth on the seasonal variations in fine root growth should be taken into account when modelling the carbon, water and nutrient cycles in forests growing on deep tropical soils.
Keywords: Fine root dynamics; Lifespan; Minirhizotron; Oxisol; Plantation; Turnover